A dynamic stochastic general equilibrium model estimated for the Costa Rica economy (2006-2014) - Valerio Berrocal, Marco Vinicio (2016)
This paper presents a specification and estimation of a dynamic stochastic general equilibrium model (DSGE), i.e. Bayesian methods that overcome the criticism by Lucas (1976), Sims (1980), and Learmer (1991). In addition, monetary policy simulations are conducted.